Reverse mortgage participation in the United States: Evidence from a national study - Swarn Chatterjee (International Journal of Financial Studies, 2016)
This paper uses the most recent wave of a nationally representative dataset to examine the factors associated with elderly homeowners' decision to obtain reverse mortgage loans. The findings of this study suggest that very few homeowners participated in the reverse mortgage market, and homeowners younger than 67 were less likely to have reverse mortgage loans. However, homeowners who were risk averse, and homeowners in the two highest quartiles of net worth were more likely to have reverse mortgage loans. Further analyses reveal that among the reverse mortgage participants, homeowners with long-term care insurance coverage were less likely to have reverse mortgage loans. Implications for financial economists, financial planners, policy-makers, and scholars of retirement economics are included.
Keywords: D91; E21; G21; J14; R21; 330; reverse mortgage; household wealth; financial decisions; retirement planning